Trauma induces overexpression of Cx43 in human fetal membrane defects†. (1st August 2017) - Barrett, David W.; Kethees, Aumie; Thrasivoulou, Christopher; Mata, Alvaro; Virasami, Alex; Sebire, Neil J.; Engels, Alex C.; Deprest, Jan A.; Becker, David L.; David, Anna L.; Chowdhury, Tina T.
Abstract: Objective: We developed an in vitro model to examine whether trauma induces connexin 43 (Cx43) expression and collagen organisation in the amniotic membrane (AM) of fetal membrane (FM) defects. Method: Term human FM was traumatised in vitro . Cell morphology and Cx43 were examined in the wound edge AM by immunofluorescence (IMF) confocal microscopy and compared to control AM. Collagen microstructure was examined by second harmonic generation (SHG) imaging. Cell viability was assessed with calcein and ethidium staining. Results: After trauma, the AM showed a dense region of cells, which had migrated towards the wound edge. In wound edge AM, Cx43 puncta was preferentially distributed in mesenchymal cells compared to epithelial cells with significant expression in the fibroblast layer than epithelial layer ( p < 0.001). In the fibroblast layer, the collagen fibres were highly polarised and aligned in parallel to the axis of the wound edge AM. There was an absence of cell migration across the defect with no healing after 168 h. Cell viability of the FM after trauma was maintained during culture. Conclusion: Cx43 overexpression in wounded AM drives structural changes in collagen that slows down efficacy of cell migration across the FM defect. © 2017 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's already known about this topic? After fetal surgery, the human fetal membrane shows limited healing and overexpression of Cx43 at the wound edge. Cx43 knockdown leads to accelerated wound healing by influencing cell migration and tissue dynamics. What does this study add? We developed an artificial fetal membrane model to examine Cx43 expression after trauma and changes in collagen dynamics. We observed Cx43 overexpression and polarised collagen at the wound edge. These changes were found to be similar to human fetoscopic wounds after fetal surgery.